2021
DOI: 10.1111/myc.13241
|View full text |Cite
|
Sign up to set email alerts
|

Azole resistance in Aspergillus isolates by different types of patients and correlation with environment ‐ An Italian prospective multicentre study (ARiA study)

Abstract: Background A wide range of frequency of azole‐resistance in A fumigatus in different patient populations worldwide was observed threatening to reduce therapeutic options. Objectives Estimate the prevalence of azole‐resistance, investigate the molecular mechanisms of resistance, compare the genotypes of resistant clinical isolates with those from the surrounding environment. Methods Aspergillus isolates were collected by seven Italian hospital microbiology laboratories. Strains were isolated from different clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In comparison to other surveillance studies, our azole resistance prevalence was higher than the 3.2% found in 2009 to 2011 in a multicentre study with 19 countries, 31 but lower than the 11% in the more recent Dutch nationwide surveillance in 2017 and 2018 22 . Larger studies and surveillances on azole resistance in A. fumigatus are summarised in Table 3 22,25,32–39 . These studies show that the azole resistance prevalence in the present surveillance is in line with other European studies from 2011 to 2018 and the Netherlands from 2007 to 2009.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In comparison to other surveillance studies, our azole resistance prevalence was higher than the 3.2% found in 2009 to 2011 in a multicentre study with 19 countries, 31 but lower than the 11% in the more recent Dutch nationwide surveillance in 2017 and 2018 22 . Larger studies and surveillances on azole resistance in A. fumigatus are summarised in Table 3 22,25,32–39 . These studies show that the azole resistance prevalence in the present surveillance is in line with other European studies from 2011 to 2018 and the Netherlands from 2007 to 2009.…”
Section: Discussionsupporting
confidence: 86%
“…22 Larger studies and surveillances on azole resistance in A. fumigatus are summarised in Table 3. 22,25,[32][33][34][35][36][37][38][39] These studies show that the This study is associated with both strengths and limitations. The primary strength is that it is nationwide and thus population based.…”
Section: Re Sultsmentioning
confidence: 97%
“…14,15 In addition, the dispersal activity of ARAf spores leads to geographical transfer is an argument in support of the emergence of these cross-resistant isolates in different countries. 14,[16][17][18][19][20] One major mechanism of azole resistance in A. fumigatus is mutations in the target enzyme sterol demethylase (cyp51A) gene. The enzyme 14-sterol demethylase is the main target for triazoles encoded by the cyp51A gene.…”
Section: Introductionmentioning
confidence: 99%
“…There is a potential link between residues of azole fungicides with similar chemical structures to triazole medicines in soil and the emergence of triazole‐resistance 14,15 . In addition, the dispersal activity of ARA f spores leads to geographical transfer is an argument in support of the emergence of these cross‐resistant isolates in different countries 14,16–20 . One major mechanism of azole resistance in A. fumigatus is mutations in the target enzyme sterol demethylase ( cyp51A ) gene.…”
Section: Introductionmentioning
confidence: 99%
“…Italian data showed that azole-resistant clinical/environmental Aspergillus spp. represented 7% of the isolates [ 6 ]. The resistance mechanisms included alteration in the cyp51A gene and promoter and upregulation of its expression [ 5 ].…”
Section: Introductionmentioning
confidence: 99%